Strategi Politik Partai Nasdem Dalam Meningkatkan Elektabilitas Di Daerah Pemilihan IV DPRD Kabupaten Sidenreng Rappang - Muhammad Ardiansyah Maulidah; Ahmad Mustanir; Barisan Barisan (STISIPOL Raja Haji, 2025)
This study is motivated by the significant increase in NasDem Party's seats in Electoral District IV of the Sidenreng Rappang Regency DPRD, from one seat in 2019 to four seats in 2024. This phenomenon indicates the effectiveness of the party’s political strategies in a local context colored by patronage, clientelism, and campaign modernization. This study aims to analyze the political strategies and their implementation in increasing electability. A descriptive qualitative approach was used, employing in-depth interviews, observation, and documentation. The results show that NasDem’s success was influenced by a modernized patron-client strategy through local political brokers, selective distribution of aid, use of development issues, and close social ties with the community. This approach is strengthened by careful socio-political mapping and strengthening of grassroots party structures. These findings imply that adaptive strategies that consider local context and social relationships can significantly improve a party’s electability at the regional level. This research contributes theoretically to the development of local political strategy theory and provides practical recommendations for contextual and effective electoral strategies.